Anal cytology in immunocompetent patients with high-grade intraepithelial neoplasia (CIN II and CIN III) - Ribeiro, Marcio Erik Franco; Barbosa, Lyliana Coutinho Resende; Schnaider, Taylor Brandão (Clinical Journal of Obstetrics and Gynecology, 2020)
Introduction: Anal cancer is directly related to the presence of high-grade HPV. Immunocompromised patients have defined conducts, something which is not observed in immunocompetent patients. Objective: To study the anal cytology of patients with high-grade intraepithelial neoplasia (CINII and III) in order to propose a protocol to be followed by the Oncology Gynaecology Service at the Samuel Libânio Clinical Hospital (HCSL). Methods: Clinical, prospective, transversal and single-centered study. Sampling was by convenience within one year. A total of 150 patients were studied. Out of these, 76 were patients with high-grade cervical intraepithelial lesions diagnosed through histopathological examination of the uterine cervix (Study Group) and 74 without high-grade intraepithelial lesions and with cervical cytology negative for neoplasia (Control Group). The following variables were analyzed: age, sexarc, tobacco use, alcohol consumption, STD history (not HPV), menopause, Hormone Replacement Therapy, anal sex practice, parity, number of sexual partners and contraceptive use. Results: There was no significant difference between the number of cases in altered anal cancer oncology in the study group, in comparison with the control group. Conclusion: There were changes in the anal cytology of the study group and these should be evaluated due to the risk of dealing with pre-neoplastic anal lesion. Clinical Trials: NCT03241680.